2012
DOI: 10.1371/journal.pone.0040038
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY Regulates Bone Remodeling in Mice: A Link between Gut and Skeletal Biology

Abstract: Background & AimsGastrointestinal peptides are increasingly being linked to processes controlling the maintenance of bone mass. Peptide YY (PYY), a gut-derived satiety peptide of the neuropeptide Y family, is upregulated in some states that also display low bone mass. Importantly, PYY has high affinity for Y-receptors, particularly Y1R and Y2R, which are known to regulate bone mass. Anorexic conditions and bariatric surgery for obesity influence circulating levels of PYY and have a negative impact on bone mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 42 publications
3
47
0
2
Order By: Relevance
“…12,13 Treatment of osteoblasts in culture with PYY increased ERK signalling via the Y1 receptor; this response was diminished in the presence of an Y1 antagonist. 9 Thus, taken together, the inhibitory nature of PYY signalling on bone mass is consistent with a number of studies examining the role of the NPY system and its receptors in the regulation of bone mass (reviewed in Khor et al 14 ). Thus, recent murine studies indicate that PYY activity has a negative influence on bone.…”
Section: Gastrointestinal Peptides: Pyysupporting
confidence: 81%
See 2 more Smart Citations
“…12,13 Treatment of osteoblasts in culture with PYY increased ERK signalling via the Y1 receptor; this response was diminished in the presence of an Y1 antagonist. 9 Thus, taken together, the inhibitory nature of PYY signalling on bone mass is consistent with a number of studies examining the role of the NPY system and its receptors in the regulation of bone mass (reviewed in Khor et al 14 ). Thus, recent murine studies indicate that PYY activity has a negative influence on bone.…”
Section: Gastrointestinal Peptides: Pyysupporting
confidence: 81%
“…8 However, Wong et al 9 demonstrated that PYY À / À mice have increased bone mass, coincident with an increase in osteoblast activity. 9 The reason for this divergent phenotype is unclear; however, it is emerging that NPY/PYY effects can be context dependent, with stressors, such as cold or restraint, producing opposing effects, linked to stimulation of noradrenaline circuits. 10,11 However, the later study, demonstrating an increase in bone anabolism with PYY deletion, is consistent with a reduction in osteoblast activity and an increase in osteoclastic surface, as evident in adult-onset PYY-overexpressing mice, 9 and with previous studies showing similar responses to loss of NPY/PYY receptors.…”
Section: Gastrointestinal Peptides: Pyymentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, peptide YY, a gut-derived, satiety hormone produced by the lower GI tract, is increased postprandially after RYGB surgery and associated with bone loss in a variety of studies in adolescents [30,31]. Conflicting findings in knockout mice on the exact role of this hormone in bone metabolism imply that further investigation of peptide YY and bone loss after RYGB is needed [32]. …”
Section: Discussionmentioning
confidence: 99%
“…There is also a growing body of literature showing that bariatric surgery alters the secretion of hormones from adipose tissue (notably the adipokines leptin and adiponectin), bone-derived factors such as the osteokine osteocalcin and sclerostin, as well as from the gastrointestinal tract (notably the appetite-regulating gut hormones PYY, GLP-1 and ghrelin), all of which have been shown to have significant effects on bone homeostasis in recent studies. The majority of these data demonstrating involvement of these hormones on bone come from a series of elegant gene knockout studies in rodents [126][127][128]. Current knowledge of the extent of their involvement in any bariatric surgery-induced bone loss and the mechanisms underlying such effects is limited.…”
Section: Potential Mechanisms Of Bone Loss After Bariatric Surgerymentioning
confidence: 99%